2006
DOI: 10.1007/s00125-006-0234-3
|View full text |Cite
|
Sign up to set email alerts
|

PEGylated glucagon-like peptide-1 displays preserved effects on insulin release in isolated pancreatic islets and improved biological activity in db/db mice

Abstract: Aims/hypothesis: The rapid degradation and clearance of glucagon-like peptide-1 (GLP-1) by the enzymes dipeptidyl peptidase-IV and neutral endopeptidase 24.11 are the main impediments to the development of GLP-1 as a potential glucose-lowering agent. In this study, new enzyme-resistant polyethylene glycol (PEG)-conjugated GLP-1 analogues were designed and examined for metabolic stability and biological potency. Materials and methods: Two mono-PEGylated GLP-1 analogues, N-terminally modified N-PEG/GLP-1 and Lys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
63
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(68 citation statements)
references
References 10 publications
5
63
0
Order By: Relevance
“…The coatings chosen were carboxymethyl dextran (CMX-MNP) and diphosphate PEG chains (PEG-MNP). The PEG polymer chosen has been shown previously to reduce protein immunogenicity and enhance blood circulatory time [31][32][33].…”
Section: Resultsmentioning
confidence: 99%
“…The coatings chosen were carboxymethyl dextran (CMX-MNP) and diphosphate PEG chains (PEG-MNP). The PEG polymer chosen has been shown previously to reduce protein immunogenicity and enhance blood circulatory time [31][32][33].…”
Section: Resultsmentioning
confidence: 99%
“…The polymers used in conjugation usually have stimuli-responsiveness, imparting unique properties into the conjugated drug such that, its activities can be turned on or off by external signals. For example, Shimoboji et al, (41,42) reported that, the catalytic activity endoglucanase 12A upon conjugation could be turned on by application of UV light or high temperature because, it was conjugated with either photosensitive or thermo-sensitive polymers. The active site of the enzyme was exposed by collapsing the conjugated long polymer chain by external stimuli.…”
Section: Polymer-drug Conjugatesmentioning
confidence: 99%
“…[12][13][14] PEGylation-covalent modification with polyethylene glycol (PEG) -is viewed as a practical way of improving the therapeutic values of antidiabetic peptides/proteins. [15][16][17][18][19] It has been well documented that this biotechnique increases metabolic resistance 20 and decreases renal clearance/tissue affinity. 21 Moreover, PEGylated peptides can modulate their in vivo pharmacokinetic profiles by simply changing the Mw of the pendant PEG, and thus increased PEG Mw enhances the aforementioned in vivo properties.…”
Section: Introductionmentioning
confidence: 99%